2021
DOI: 10.3390/biom11071063
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial Microcirculation Is a Major Target of SARS-CoV-2-Mediated Vascular Inflammation

Abstract: We report the case of a 77-year-old woman affected by coronavirus disease-19 (COVID-19) who developed an occlusive arterial disease of the lower limb requiring a left leg amputation. We studied the mechanisms of vascular damage by SARS-CoV-2 by means of a comprehensive multi-technique in situ analysis on the diseased popliteal arterial district, including immunohistochemistry (IHC), transmission electron microscopy (TEM) and miRNA analysis. At histological analyses, we observed a lymphocytic inflammatory infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Fibrin microthrombi near pericytes were noted in the lungs. Another study reported the development of an occlusive arterial disease requiring lower left limb amputation and, upon histological examination, identified lymphocytic infiltrate and edema of adventitial vasa vasorum ( 203 ). More recently, multiple occlusive microthrombi were noted in the vasa vasorum amidst numerous atherosclerotic plaques in the aorta of a patient with a fatal COVID-19 infection ( 204 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin microthrombi near pericytes were noted in the lungs. Another study reported the development of an occlusive arterial disease requiring lower left limb amputation and, upon histological examination, identified lymphocytic infiltrate and edema of adventitial vasa vasorum ( 203 ). More recently, multiple occlusive microthrombi were noted in the vasa vasorum amidst numerous atherosclerotic plaques in the aorta of a patient with a fatal COVID-19 infection ( 204 ).…”
Section: Introductionmentioning
confidence: 99%
“…While data is sparse, Pasquinelli et al showed, through histological analysis, that adventitial microcirculation is a major target of SARS-COV-2 mediated vascular inflammation. In their case they found that endothelial inflammation was most prevalent in the perivascular microcirculation as endothelial cells are primary targets of the SARS-Cov-2 virus [ 14 ]. It is impossible to know for fact, but in our patient, there may have been a component of localized microcirculatory thrombosis and subsequent adventitial fibrosis that resulted in our cannula becoming adhered to the luminal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several dysregulated miRNA including 4 down-regulated miRNAs (miR-486-5p, miR-451a, miR-206, and miR-142-5p) and 5 up-regulated miRNAs (miR-155-3p, miR-27a-5p, miR-20a-5p, miR-17-5p, and miR-107) were associated with pathophysiology in response to viral replication (42-49). Among them, miR-486-5p, miR-451a, miR-142-5p, miR-27a-5p, miR-20a-5p, miR-17-5p have been reported to be dysregulated in SARS-CoV-2-infected patients (50)(51)(52)(53), while others such as miR-206, miR-155-3p and miR-107 have not been associated with SARS-CoV-2 viral infection, suggesting that host miRNAs reacting at early stage of SARS-CoV-2 infection might play important roles in host-SARS-CoV-2 interaction.…”
Section: Host Mirnas React To Sars-cov-2 Infections In Vero Cellsmentioning
confidence: 99%